Green Accounting Memoderasi Material Flow Cost Accounting terhadap Peningkatan Keberlangsungan Perusahaan - Muanifah, Suciati; Cahyani, Yenni (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
This study aims to test and find out the material flow cost accounting in increasing the sustainability of the company. In addition, this study also aims to test whether the green accounting variable moderates the relationship between each MFCA variable (production costs, and production yield/value) in increasing the sustainability of the company. The sample used in this research is energy companies listed on the Indonesia Stock Exchange (IDX) during the 2017-2022 period. The total sample is 55 out of 11 companies using a purposive sampling technique. Methods of data analysis using multiple regression and moderating regression analysis with the absolute difference value approach. Multiple linear regression analysis for the MFCA hypothesis (production costs, and production yield/value). Multiple linear regression analysis with absolute difference value test for the MFCA hypothesis (production costs, and yield/production value) moderated by green accounting. The results of the study show that MFCA (production costs) has no effect on green accounting. MFCA (Production Results) has a positive effect in increasing the sustainability of the company. The results of research related to moderating variables show that green accounting as a moderating variable strengthens the relationship between MFCA (yield/production value) in increasing company sustainability. Conversely, in the fourth and fifth hypotheses, green accounting weakens the MFCA (production costs) relationship in increasing the sustainability of the company.